Expectation Gaps and Halo-Effects in Organic Food Positioning: Characteristics of Organic Food from a Consumer's Point of View - Marie von Meyer-Höfer; Sina Nitzko; Achim Spiller (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
Despite the different levels of maturity of organic markets among the member states of the European Union (EU), the European organic food market is continuously growing. In the EU this production method is regulated according to the Council Regulation (EC) 834/2007 (EC 834/07). All products produced accordingly are labelled with the common European organic label. The future success of organic agriculture as one sustainable solution of food production is to a large extent dependent on its market success, thus the positioning of organic food is a crucial topic for food policy and marketing. This paper analyses the data of an online survey done in 2011 with a total of 1,180 consumers from four European countries (Germany, United Kingdom, Spain, and Czech Republic,) representing different stages of the current organic market development across Europe. This paper focusses on which criteria consumers attach to organic food products and what attributes they expect of them. The risk that consumers might expect too much of organic food produced under EC 834/07 is identified. To overcome the observed expectation gap, some political as well as practical implications are proposed.
Keywords: Q01; Q13; Q18; Q19; 330; organic food; positioning; expectation gap; halo-effect